Efektivitas Metode Ceramah plus Demonstrasi dan Latihan dalam Meningkatkan Pemahaman Ubudiyah Santriwati pada Program Kuliah Subuh - Firda Diana; Firda Ayu Wahyuni (Fakta: Jurnal Pendidikan Agama Islam, 2021)
One of the Teacher’s efforts to overcome some of the weaknesses of the lecture method is to combine it with several other methods,one of them is the lecture method plus demonstrations and exercises, that combines the activities of describing the subject matter with demonstration and training activities (drill). The purpose of this study was to find out how the practice of amaliyah using lectures plus demonstrations and exercises in the program kuliah subuh and to describe the effectiveness of the lecture plus demonstration and training methods in increasing the understanding of the students’ ubudiyah. The method used is qualitative case study. And determining the informants in this study using purposive sampling method,  data analysis from Miles and Huberman namely the data analysis process carried out simultaneously with the data collection process. As for the results of this study indicate that the implementation of the lecture plus demonstration method and exercise starts from the activities of describing the Subject, that has been explained and finally holding repeated exercises. So that the application of the lecture plus demonstration method and exercise can be considered quite effective in the Kuliah Subuh program at Nurulhuda Islamic Boarding School because it can focus the attention of students so that they can focus and not be sleepy.